Ground reaction forces in simulated figure skating jump takeoffs and landings - Kho, M.; Bishop, P. J. (1998)
The magnitude of peak vertical ground reaction landing forces in this study were similar to those reported by McNitt-Gray (1993) and Foti (1990). Maximum vertical ground reaction takeoff forces were considerably smaller than those of gymnasts (Miller et al., 1987). This was reasonable, because the gymnasts approached their takeoffs from a running start and propelled themselves into the air with both feet. Figure skating jumps also involve axial rotation; skaters must initiate rotation with a horizontal and torsional forces in addition to vertical force. Vertical forces alone do not provide insight into potential injury mechanisms in figure skating. This study was part of a larger project that used a link segment biomechanical model to determine bone-on-bone forces at the ankle and knee in loop jump takeoffs and landings.